Urbana drevnina in skrb zanjo v Lescah - Neve Repe, Andreja (Gozdarski vestnik, 2008)
We made an inventory of trees and shrubs in Lesce, which included 725 individuals. They comprised mainly trees (79.8 %), while shrubs were less abundant (20.2 %). Each individual was given a serial number, and the following characteristics were recorded: location; dimensions (height and diameter at breast height); vitality: visible damage; and recommendations for further tending. In Lesce young, recently planted trees and shrubs were common(58.2 %), for which we suggested 171 or 75.3 % from all measures. Old trees were not vital, and 84.6 % of them showed damage. Among the inhabitants of Lesce we made a survey regarding their opinion toward trees and shrubs and green spaces in Lesce. We discovered that residents wanted greenery in their environment but they needed suggestions and help from professionals regarding maintenance, care and planting. We found that there was no difference between people who were involved in maintaining greenery and those who were not.
Keywords: forestry; gozdarstvo; mestni gozdovi; drevesa; grmovnice; Lesce